Microencapsulation of Vaccine Antigens and Adjuvants for Mucosal Targeting - Rajapaksa, Thejani E.; Lo, David D. (Current Immunology Reviews (Discontinued), 2010)
Delivery of vaccine antigens that can trigger potent mucosal immune response is one of the effective strategies to overcome a wide array of infectious diseases. Microencapsulation of vaccine antigens with Poly(lactide-co-glycolic acids) (PLGA), an FDA approved biodegradable polymer, has been investigated for targeted M-cell uptake. While PLGA possesses many attractive properties, a successful PLGA based mucosal-targeted vaccine has yet to be introduced. This review focuses on the physiochemical properties important in the preparation of antigen-loaded PLGA microparticles, properties that influence M-cell specific uptake, and the induction of effective immune responses. In addition, a possible role of microparticle properties in immune adjuvant activity is discussed. A careful consideration of these factors may yet lead to the development of an effective needle-free mucosal vaccine using polymer microparticles.
Keywords: PLGA